2021
DOI: 10.3390/pharmaceutics13050660
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with Microbial Proteins Driving the Antibacterial Activity of Flavonoids

Abstract: Flavonoids are among the most abundant natural bioactive compounds produced by plants. Many different activities have been reported for these secondary metabolites against numerous cells and systems. One of the most interesting is certainly the antimicrobial, which is stimulated through various molecular mechanisms. In fact, flavonoids are effective both in directly damaging the envelope of Gram-negative and Gram-positive bacteria but also by acting toward specific molecular targets essential for the survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 128 publications
(146 reference statements)
3
28
0
Order By: Relevance
“…Some compounds aim for the efflux mechanisms in Gram negative bacteria to regulate drug resistance. 22 In this study, we determined the antibacterial activities of essential oils of M. cajuputi against Gram positive (S. aureus, S. pyogenes, and MRSA) and Gram negative (K. pneumoniae and E. coli) bacteria using the disc diffusion and MIC assays. The results revealed that the essential oils of M. cajuputi intensively inhibited Gram positive bacteria compared to Gram negative bacteria, wherein the inhibition zones against Gram positive bacteria were greater than those in Gram negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Some compounds aim for the efflux mechanisms in Gram negative bacteria to regulate drug resistance. 22 In this study, we determined the antibacterial activities of essential oils of M. cajuputi against Gram positive (S. aureus, S. pyogenes, and MRSA) and Gram negative (K. pneumoniae and E. coli) bacteria using the disc diffusion and MIC assays. The results revealed that the essential oils of M. cajuputi intensively inhibited Gram positive bacteria compared to Gram negative bacteria, wherein the inhibition zones against Gram positive bacteria were greater than those in Gram negative bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The microbial proteins affected by phenolic compounds belong to membrane (efflux system, cell envelope metabolism, and ATP synthase system), anabolic and catabolic reactions, pathogenic and antibioticresistance mechanisms, such as toxins and virulence factors transporters and antibiotic-inactivating enzymes, virulence factors, biofilm, and DNA metabolisms. Bacterial cell membrane is a complex system that plays roles as barrier between outside and inside of the cell, regulator of the osmotic, energy, and lipid systems, as well as cell wall maintenance (104). The major antibiotics, including penicillins, cephalosporins, and polymixins, target the bacterial membrane and cell wall, thus disrupting their functions and leading to bacterial death.…”
Section: Implications Of Dietary Phenolic On Microbiota and Microbial...mentioning
confidence: 99%
“…For example, the flavonoids kaempferol, chrysin, quercetin, baicalein, luteolin, epigallocatechin gallate, gallocatechin, theaflavin, and theaflavin gallate, when in contact with the bacterial cell membrane, decrease its fluidity, while the isoflavonoids puerarin, ononin, daidzein, genistein, and the stilbene resveratrol have shown the opposite effect [90,91]. Destabilitization of the bacterial cell membranes could also result from phenolics stepping into reaction with enzymes responsible for cell membrane stability and integrity [68,94]. In addition, some phenolic acids (caffeic and gallic acids) acidify the bacterial membrane, leading to its disruption and changes in permeability and ion transport [95].…”
Section: Interaction With Bacterial Cell Walls Cell Membranes and Synergism With Antibioticsmentioning
confidence: 99%
“…In general, the biologically active aglycons of phenolic compounds possess a structure rich in reactive functional groups, multiple phenolic groups, carbonyl groups (e.g., xanthones, anthraquinones, most flavonoids), free or esterified carboxylic groups (phenolic acids), among others. They easily step into hydrogen bonding with other biomolecules (nucleotides, proteins, including adhesins and receptors, enzymes as DNA/RNA polymerases and topoisomerases, transcriptases, proteases, and many others) [94,98,99] or complexation with metal ions (iron ions) [100] that are essential for the infectious cycle of pathogenic bacteria and viruses (adhesion, entry, replication and spread) [84,101]. This is a wideranging and nonspecific complex of potential interactions of phenolics that has led many researchers to understand their antiviral and antibacterial properties.…”
Section: Interaction With Bacterial Cell Walls Cell Membranes and Synergism With Antibioticsmentioning
confidence: 99%